FIQIH DAKWAH DALAM KISAH-KISAH SURAT AL-KAHFI - Mohammad Bashri Asyari (UIN Mataram, 2019)
Da'wah on the basis of inviting humans back to their original nature, accepts the oneness and divinity of Allah SWT. This task is not only mandated for the Prophets and Apostles, but is mandated for humanity who have believed in Him. The stories translated in Surat al-Kahf with the preachers of non-Prophets and Apostles, are the best examples of devotees who support the exploration of preaching that need to be explored by instructions, lessons and substantive messages to be spoken and practiced at this time. This limits the research studies on the verses on the four stories in Surat al-Kahf which contain the essence of the fiqh of da'wah, and does not discuss the details of the stories because this has been extensively studied and discussed in classic or modern commentary books.